Formas de tratamiento e interferencia. Estudio sobre el uso de las formas de tratamiento españolas por parte de portugueses nativos residentes en Madrid - Granvik, Anton (Revista de Filología Románica, 2008)
The aim of the study is to investigate the phenomenon of linguistic interference in a situation of language contact between peninsular Spanish and Portuguese. The research focuses on the differences between the systems of address terms of both languages, and special reference is made to the influence of the Portuguese system on the L2 use of Spanish by native speakers of Portuguese. On the basis of a small empirical corpus that was collected using a questionnaire directed to university students in Madrid, native Portuguese students residing in Madrid as well as students from the Portuguese city of Porto, it can be observed how the more frequent use of V-forms in Portuguese clearly reflects itself in an excessive use of usted by native speakers of Portuguese while speaking Spanish in comparison to native Spanish speakers.